Online System Adaptation Single Submission Risk Based Approach (OSS-RBA) - Kristantiya, Triambodo Andi; Sudarmo, Sudarmo; Sudibyo, Desiderius Priyo (Future Science / FSH-PH Publications, 2023)
The industrial revolution can bring changes in human lifestyles, from manual to digital trading and ways of working. This will provide Indonesia with opportunities, enormous opportunities, including government organizations that are innovative in fulfilling their mandates and functions. Utilizing developments in information technology, accelerating the promotion of e-government, implementing science and technology public services and implementing other government affairs. The Indonesian government has finally passed Law No. 19 of 2020. Law Number 11 of 2020 concerning Job Creation has changed the licensing paradigm from a permit-based approach to a risk-based approach (RBA). Not without reason, this provision is intended to provide ease and certainty in doing business so as to increase regional competitiveness. This new paradigm places risk as the main consideration in every business activity, thus having implications for changes in the current design of business policies, institutions and service platforms in the central and regional governments. However, at the implementation level in each region, the application of this risk-based licensing model depends on the readiness and subsequent response from each region, especially policies, institutions (organization and human resources) and digital service tools (sarpras, internet networks). Electronically Integrated Business Licensing or Online Single Submission Risk-Based Approach (OSS-RBA) is a business license issued by the OSS-RBA agency on behalf of the Minister, Head of Agency, Governor, or Regent/Mayor to commercial participants through an electronic system. The OSS-RBA was created as a form of reform in the field of commercial licensing, because initially the handling of proposed permits seemed complicated, requiring lengthy bureaucratic procedures and direct visits to relevant agencies.